A Survey on the Prevalence of Dental Caries Among Elementary School Girls of Multan, Pakistan: A Cross-Sectional Study (Medical Forum Monthly, 2023)
Study Design: cross-sectional study Place and Duration of Study: This study was conducted at the Oral Biology Department, Tertiary Care Dental Hospital of Multan, Pakistan from January 2023 till June 2023. Materials and Methods: The study was conducted at an elementary school for the purpose to assess dental caries in girls after the provision of the certificate from the ethical review board. A total of 270 girls were selected by utilizing a random sampling technique and Rao soft calculator was used. The age of the participants was 8-16 years. Informed consent was obtained from each participant accordingly after translating into Urdu language. All the data were collected from questionnaires and intra-oral checkups as well. The data was analyzed by using the latest version of SPSS 24. Results: A total of 270 girls were selected in the current study with their ages ranging from 8-16 years. 93 (34.44%) of them were from 11-13 years of age and 111(41.11%) were from 14-16 years of age. The mean age of the participants was 12.13 ± 2.32 years. The overall frequency of dental caries was 166 (61.48%). 188 (96.62%) were decayed, 77 (26.66%) were missing teeth and 11 (4%) had filled teeth. 48.79% of them were from 11-13 years, 28.31% were from 8-10 years and 22.89% of them were from 14-16 years. 80.72% of them had 1-2 teeth affected, while 53.61% had 3-4 teeth affected and 42.77% of them had 5-6 teeth affected among the various age groups respectively. 34.44% had good oral hygiene. Furthermore, 56.29% had bacterial plaque bio-film. Conclusion: The current study concluded that the overall prevalence of dental caries among elementary school girls was more than half (61.48%), therefore, proper management and awareness programs need to be arranged for the school girls, parents, and the teachers so as to maintain a good oral health and minimize the prevalence of dental caries among these subjects.